Experimental study of the asymmetry of a three-phase stress system - Abdieva Z.E.; Sariev B.I.; Kurzhumbaeva R.B.; Kasmambetov K.T. (Научно-технический вестник Брянского государственного университета)
“Arduino” allows the computer to simulate the electrical load. Devices using “Arduino” receive sensor information and control the actuators. The platform, with software code, is built on a simple board with a modern environment for writing software. This modern device was used in the developed experimental installation at the Department of Electric Power Supply of the Kyrgyz State Technical University named after I. Razzakova, for the study of physical processes in electrical networks. The investigations were carried out on an experimental setup under various conditions: a symmetric regime; asymmetric mode, with a load on two phases; unbalanced mode, with a single phase load (extreme asymmetry mode). Studies show the influence of asymmetry on the growth of electricity losses in electrical networks.